P169 Subclinical ocular manifestations of pulmonary and extrapulmonary tuberculosis in a Hampshire population. (16th November 2010) - Beeson, S; Wetherill, N; Mansour, S; Banerjee, A K; Rowen, D; Hall, N; Marshall, B G
Abstract : Background: Intraocular tuberculosisis capable of imitating numerous uveitis entities; the ability of TB to causeuveitis is multi-factorial including virulence of the infecting organism, anindividual's immune response, and the location of the disease. The non-specificnature of uveitis makes diagnosis difficult, and allowed to progressunchallenged, intraocular tuberculosis can be sight-threatening. We postulate that subclinical ocular signs of TB might coexist with TB activeat other sites. Methods: 14 TB latent, 14 TB active, and 3 TB-HIV co-infected patients were recruited for this pilot study, between October 2009 and April 2010, from the TB service at the Royal South Hants Hospital. At Southampton General Hospital's Eye Unit patients provided detailed ocular and tuberculosis histories; all patients then underwent a series of extensive ocular examinations, including best corrected visual acuity and colour vision, intraocular pressure, pupillary response, ocular motility, slit lamp and dilated fundus examinations; finally each patient's ocular findings were correlated against their TB and TB-HIV co-infection clinical profiles. Results: 14 patients were classified "latent TB" (IGRA positive, asymptomatic) and 14 patients were classified "active TB" (symptoms, culture positive) of whom three were "TB-HIV co-infected". Patients with active TB were identified as having significantly more symptoms associated with anterior uveitis, such as pain, photophobia, redness and blurred vision/floaters, compared to those patients with latent TB. We demonstrated objective evidence of anterior chamber inflammation inpatients with active disease, but not latent disease. The patients with HIV coinfection exhibited combined anterior and posterior segment abnormalities consistent with an active uveitis. Conclusions: The results of this pilot study suggest that patients with active TB have symptoms suggestive of uveitis, but these are unrecognised by the patient unless specifically sought. These patients have anterior chamber findings of uveitis. TB-HIV co-infected patients appear to present asymptomatically with anterior segment and potentially posterior segment signs. These findings suggest that units treating TB should actively screen all patients newly presenting with TB for occult ocular disease.